Daratumumab, Bortezomib, and Dexamethasone for treatment of patients with relapsed or refractory multiple myeloma and severe renal impairment: results from the phase 2 GMMG-DANTE trial - Leypoldt, Lisa; Gavriatopoulou, Maria; Besemer, Britta; Salwender, Hans; Raab, Marc-Steffen; Nogai, Axel; Khandanpour, Cyrus; Runde, Volker; Jauch, Anna; Zago, Manola; Martus, Peter; Goldschmidt, Hartmut; et al. (Cancers, 2023)
Renal function impairment (RI) is a common complication in multiple myeloma (MM). However, limited data exist on the safety and efficacy of anti-MM regimens in patients with severe RI, as these patients are frequently excluded from clinical trials. This investigator-initiated multicentric phase II GMMG-DANTE trial evaluated daratumumab, bortezomib, and dexamethasone (DVd) in relapsed or refractory (r/r) MM patients with severe RI. r/rMM patients with ≥1 prior treatment line and a GFR <30 mL/min/1.73 m2 or undergoing hemodialysis were eligible and received eight cycles of DVd followed by daratumumab maintenance. The trial closed prematurely after 22/36 planned patients. The primary endpoint was overall response rate (ORR). Median age of patients was 70 (range 55-89) years, with a median GFR of 20.1 mL/min/1.73 m2 (interquartile range, 9.4-27.3 mL/min/1.73 m2), and eight patients under hemodialysis. Median number of prior lines was two (range 1-10). The trial was successful, albeit with premature termination, as it met its primary endpoint, with an ORR of 67% (14/21). The rates of partial response, very good partial response, and complete response were 29%, 29%, and 10%, respectively (n = 6, 6, and 2). Fourteen patients (67%) achieved renal response. After median follow-up of 28 months, median progression-free survival was 10.4 months; median overall survival was not reached. Higher-grade toxicity was mainly hematologic, and non-hematologic toxicities ≥Grade 3 were mostly infections (24%). The prospective GMMG-DANTE trial investigating DVd exclusively in r/rMM patients with severe RI showed efficacy and safety to be comparable to data from patients without RI.